The rise of flexible electronics in neuroscience, from materials selection to in vitro and in vivo applications. Issue 1 (1st January 2019) - Maiolo, L.; Polese, D.; Convertino, A.
ABSTRACT: Neuroscience deals with one of the most complicate system we can study: the brain. The huge amount of connections among the cells and the different phenomena occurring at different scale give rise to a continuous flow of data that have to be collected, analyzed and interpreted. Neuroscientists try to interrogate this complexity to find basic principles underlying brain electrochemical signalling and human/animal behaviour to disclose the mechanisms that trigger neurodegenerative diseases and to understand how restoring damaged brain circuits. The main tool to perform these tasks is a neural interface, a system able to interact with brain tissue at different levels to provide a uni/bidirectional communication path. Recently, breakthroughs coming from various disciplines have been combined to enforce features and potentialities of neural interfaces. Among the different findings, flexible electronics is playing a pivotal role in revolutionizing neural interfaces. In this work, we review the most recent advances in the fabrication of neural interfaces based on flexible electronics. We define challenges and issues to be solved for the application of such platforms and we discuss the different parts of the system regarding improvements in materials selection and breakthrough in applications both for in vitro and in vivo tests. Graphical Abstract: